Allegory and Democratic Public Culture in the Postmodern Era. - Hariman, Robert (Philosophy & Rhetoric, 2002)
The article informs that allegory arises when Greek rationality overpowers archaic myth, when Christendom engulfs pagan culture, when early modern thought displaces Christian hegemony, when modernization destroys traditional social order, when late-modern technocracy colonizes the life world. This history is itself allegorical. To the extent that allegory is an omnipresent mode of symbolizing, it is the mode that is resolutely liminal. Allegories are exercises in necessarily imperfect translation between such incommensurable realms as cosmology and history, myth and interpretation, image and idea, past and present, theory and praxis, author and interpreter. The consciousness of the mass media is one in which all ages are contemporaneous within the natural attitude of the present, which makes any sign of the past but a fragment of a lost totality. Such developments provide an extremely high degree of inventional freedom for those in discourse production, as they also disable virtually any appeal to or attempt to stay within a tradition. Perhaps it is more accurate to say that postmodern culture operates through allegorical designs but without any didactic intention.